Dominica. Significant achievements 2021 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Dominica during 2021 are identified, with respect to the needs and interests of the country, strengthening on issues such as resilience to climate change, microfinance for small and microenterprises, food safety and security, biodiversity, sustainability, resilience of agricultural land and forests, composting. Likewise, artisans were supported through activities that allowed them to sell their products. Finally, work was done to address the problems caused by COVID-19; in the implementation of new technologies in agriculture and in digital commerce; as well as in the inclusion of women producers.